Facile Fabrication, Structures, and Properties of Laser‐Marked Polyacrylamide/Bi2O3 Hydrogels1 . Issue 5 (8th February 2017) - Cao, Zheng; Hu, Yanchao; Yu, Qiang; Lu, Ying; Wu, Dun; Zhou, An; Ma, Wenzhong; Xia, Yanping; Liu, Chunlin; Loos, Katja
Abstract : Laser marking of wet and soft polyacrylamide/bismuth oxide (PAM/Bi2 O3 ) hydrogel materials can be achieved by simply embedding Bi2O3 particles inside PAM hydrogels and a subsequent laser treatment with a Nd: YAG laser beam at 1064 nm. In comparison with the pure hydrogel, the marking properties of the laser‐marked PAM/Bi2 O3 hydrogel samples vary as the Bi2 O3 content increase from 0.17 to 3.0 wt% and as the laser power increase from 23.5 to 47.0 W. SEM, XPS, XRD, TGA, Raman spectroscopy, water contact angle and mechanical property tests are performed to characterize the laser‐marked PAM/Bi2 O3 hydrogels. The results herein indicate that the marking contrast and visual appearance on the surface of the PAM/Bi2 O3 hydrogels after laser irradiation are mainly due to the decomposition of Bi2 O3 to black bismuth metal. Abstract : Laser marking of wet and soft PAM/Bi2 O3 hydrogel materials can be achieved by simply embedding Bi2 O3 particles inside PAM hydrogels and a subsequent laser treatment. The marking properties of hydrogels are determined by the Bi2 O3 content and the laser power employed. The facile method is very promising for applications including the marking and decoration of soft and wet hydrogel products.